DISTRIBUTION OF PHYTOPLANKTON IN THE ARABIAN SEA BETWEEN CAPE COMORIN AND COCHIN - Chennubhotla, V S K (Indian Journal of Fisheries, 2011)
The phytoplankton samples collected from the continental shelf and offshore waters of the region between Cape Comorin and Cochin during the cruises of R. V. Varuna in 1964-65 were studied by displacement volume and dryweight methods, and the values were represented by isolines to find out the relative abundance of the phytoplankton in the different regions in the different months. Phytoplankton was found to be abundant in the months of May and June in the areas between 8°—10° N and 75°—77° E in terms of displacement volume and dry weight. The estimated values for this region are higher than those values obtained for areas like the English Channel and Gulf of Maine at the height of bloom there.